Empirical study on the impact of digital economy on carbon emission intensity–based on the mediating role of technological innovation - Yan, Xiaoxia; Zhang, Yan (Frontiers in Energy Research, 2023)
With the proposal of "Carbon Peak and Carbon Neutrality" goals, China is facing a more serious carbon emissions reduction situation, and how the booming digital economy effectively helps China's carbon emissions reduction is one of the most urgent things that should be solved. To study the impact of the digital economy on carbon emission intensity, this paper is based on the panel data of 30 provinces in China (excluding Tibet, Hong Kong, Macao, and Taiwan) from 2011 to 2021, and applies the double fixed effect model and the threshold effect model to study the impact of the digital economy on carbon emission intensity and the mechanism of its action, as well as to analyze the mechanism of the digital economy's action on carbon emission intensity from the perspective of technological innovation. The results of the study show that: (i) The digital economy can reduce the intensity of regional carbon emissions; (ii) The carbon emission reduction effect of the digital economy is non-linear, and its carbon emission reduction effect gradually increases with the level of development of the digital economy; (iii) In addition to the direct impact of the digital economy on carbon emission intensity, it also has an indirect impact on carbon emissions through technological innovation; (iv) There is regional heterogeneity in the carbon emission reduction effect of the digital economy, and the carbon emission reduction effect is more significant in the central and western parts of the country and regions with a high level of human capital development. Based on the conclusions obtained, this paper suggests that: the rational integration of the digital economy and regional development should be strengthened; strong provinces in the digital economy should be encouraged to help weaker provinces, to narrow the "digital divide" between provinces; and differentiated development strategies should be formulated in accordance with local conditions, to give full play to the optimal effect of the digital economy in carbon emission reduction.